THE ROLE OF KOMIL KHOREZMI IN THE HISTORY OF THE KHIVA KHANATE - Allanazarov Shoxruxbek Farxodovich; Otaboyev Xamdambek Davranbek o‘g‘li (Bright Mind Publishing, 2026)
This article analyzes Komil Khorezmi's role in the Khiva Khanate, his contributions to literature, art, and culture, as well as his active participation in the Jadid movement. It provides information about his activities in the politics of the Khiva Khanate.
Keywords: Mahofil miro, Mirza, Devonbegi (Title - remains Devonbegi, a high-ranking official), Printing House (for Bosmaxona), Peshravi Feruz (Proper name - remains Peshravi Feruz), Divans or Poetry Collections (for Devonlar), Rost Maqom (Name of a musical mode - remains Rost Maqom), Ghazal (Poetic form - remains Ghazal), Murabba (Poetic form - remains Murabba).